Using performance standards to guide vernal pool restoration and adaptive management. Issue 2 (22nd January 2016) - Schlatter, Karen J.; Faist, Akasha M.; Collinge, Sharon K.
Abstract : Although many restoration projects now include monitoring and evaluation in an adaptive management approach, a failure to employ distinct performance standards can lead to inconsistent and unclear results that may hinder learning from project outcomes and complicate large‐scale assessments of restoration success. Such is the case with vernal pool restoration projects in California, where performance standard guidelines are vague and inconsistently applied across agencies implementing restoration projects. However, positive steps have been made in recent years to develop wetland functional assessments and monitoring protocols in California to reduce inconsistencies and promote ecologically meaningful restoration. Additional work is needed to develop specific guidelines for vernal pool restoration performance standards and define their role within an adaptive management framework. We provide a case study of a vernal pool restoration project in central California to illustrate some of the challenges in using currently available vernal pool performance standard guidelines and propose suggestions for increasing their ecological relevance and clarity.